Combined effects of low-intensity blood flow restriction training and high-intensity resistance training on muscle strength and size - Yasuda, Tomohiro; Ogasawara, Riki; Sakamaki, Mikako; Ozaki, Hayao; Sato, Yoshiaki; Abe, Takashi (European journal of applied physiology, 2011)
We investigated the combined effect of low-intensity blood flow restriction and high-intensity resistance training on muscle adaptation. Forty young men (aged 22–32 years) were randomly divided into four groups of ten subjects each: high-intensity resistance training (HI-RT, 75% of one repetition maximum [1-RM]), low-intensity resistance training with blood flow restriction (LI-BFR, 30% 1-RM), combined HI-RT and LI-BFR (CB-RT, twice-weekly LI-BFR and once-weekly HI-RT), and nontraining control (CON). Three training groups performed bench press exercises 3 days/week for 6 weeks. During LI-BFR training sessions, subjects wore pressure cuffs on both arms that were inflated to 100–160 mmHg. Increases in 1-RM were similar in the HI-RT (19.9%) and CB-RT (15.3%) groups and lower in the LI-BFR group (8.7%, p < 0.05). Maximal isometric elbow extension (MVC) increased in the HI-RT (11.3%) and CB-RT (6.6%) groups; there was no change in the LI-BFR group (−0.2%). The cross-sectional area (CSA) of the triceps brachii (TB) increased ( p < 0.05) in the HI-RT (8.6%), CB-RT (7.2%), and LI-BFR (4.4%) groups. The change in relative isometric strength (MVC divided by TB CSA) was greater ( p < 0.05) in the HI-RT group (3.3%) than in the LI-BFR (−3.5%) and CON (−0.1%) groups. Following training, relative dynamic strength (1-RM divided by TB CSA) was increased ( p < 0.05) by 10.5% in the HI-RT group and 6.7% in the CB-RT group. None of the variables in the CON group changed. Our results show that low-intensity resistance training with BFR-induced functional muscle adaptations is improved by combining it with HI-RT.